Randomised study within a trial (SWAT) to evaluate personalised versus standard text message prompts for increasing trial participant response to postal questionnaires (PROMPTS) - Cureton, LA; Marian, IR; Barber, VS; Parker, A; Torgerson, DJ; Hopewell, S (BioMed Central, 2021)
Background: Use of a person’s name in a text message has been shown to be effective in instigating behaviour change. We evaluated the effectiveness of a personalised text message (including the recipient’s name) versus a standardised text message for prompting a response from trial participants to complete and return postal follow-up questionnaires.